A Macro-Distinct Element Model (M-DEM) for out-of-plane analysis of unreinforced masonry structures. (1st October 2021) - Malomo, D.; DeJong, M.J.
Highlights: M-DEM capabilities extended towards the modeling of OOP mechanisms of URM systems. First hybrid FEM/DEM macroelement to enable explicit low-cost simulation of OOP failures. Ad-hoc analytical pre-processing procedure devised for further decreasing analysis time. M-DEM validated against one-way and two-way bending static and dynamic tests. Experimentally-observed OOP responses adequately reproduced numerically. Abstract: Despite the vulnerability of unreinforced masonry (URM) structures to out-of-plane (OOP) loading, computational methods that can efficiently simulate OOP failure at the building scale are still limited. Current methods typically rely on simplified static analysis approaches or refined micro-modeling techniques that entail high computational expense, thus limiting their employment to reduced-scale and local problems. With a view to overcome these issues, a novel Finite-Distinct macroelement model which combines the efficiency of simplified modeling strategies with the multifaceted capabilities of discontinuum-based methods, is developed and implemented in the framework of the Distinct Element Method (DEM). Shear and flexural failure modes, either in-plane or out-of-plane, are accounted for by zero-thickness interface spring layers, whose layout is determined a priori as a function of the considered masonry bond pattern. Meanwhile, crushing failure is modeled through homogenized Finite Element macro-blocks. The proposed discretization scheme is conceived so that the model can also be used to simulate in-plane damage, for which the model has already been validated. Simplified expressions are proposed for determining equivalent mechanical properties of the interface spring layers, depending on their inclination. Similarly, analytically-based equations are used to significantly reduce the number of springs needed to adequately reproduce the OOP bending response at the joint level. Numerical simulations are compared to previous experimental quasi-static and dynamic tests on both brick and block URM components, characterized by markedly different vertical pressures, aspect ratios, boundary conditions and confinement; both one-way and two-way bending actions are considered. The results indicate that the model can satisfactorily reproduce the measured load–displacement curves in a reasonable timeframe, as well as the experimentally-observed failure mechanisms.